Measurement of the strange quark forward-backward asymmetry around the Z(0) peak - Abreu, P; Adam, W; Adye, T; Adzic, P; Abrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; Amaldi, U; et al. (2000)
A precise measurement of the strange quark forward-backward asymmetry used 3.2M multihadronic events around the Z° peak collected by the DELPHI experiment from 1992 to 1995. The ring imaging Cherenkov detectors in the barrel and end-cap regions identify high energy charged kaons which tag the s quark. The s quark asymmetry was measured at different centre-of-mass energies; m particular at the Z° pole A°ss̄ = 0.1008 ± 0.0113 (stat.) ± 0.0040 (syst.), (1) taking the expected d and u quark asymmetries from the Standard Model. The quark flavour fractions are assumed from the Standard Model and the fragmentation process is modelled by JETSET. From the s quark pole asymmetry the electroweak mixing angle was determined: sin2 θlepteff = 0.2321 ± 0.0029. (2) The parity violating coupling of the s quark to the Z was determined to be: As = 0.909 ± 0.102 (stat.) ± 0.036(syst.). (3).